KONSUMERISME DALAM PERSPEKTIF ISLAM - Eddy Rohayedi; Maulina Maulina (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2020)
Most of the world community has become a modern society, modernization has a positive impact in facilitating daily activities, and it is closely related to consumer behavior (consumerism) which is embraced by the society consciously or unconsciously. This research describes how Islam views the consumerism. The method that used in this research is descriptive qualitative, which describes the phenomena that exist about consumerism in Islamic perspective. The type of qualitative research that used in this study is the study of documents or texts, which are studies of written documentary material in the form of textbooks, manuscripts, articles, and its kind. Data analysis procedure before in the field is to analyze result on the preliminary observational study. The analysis during the field uses Miles and Huberman's model analysis, which suggests that the activities and analysis of qualitative data are carried out interactively and continuously until completion, thus the data is already saturated. Data analysis consist data collection, data reduction, data presentation, andanalysis/conclusion. The results shows that consumerism is excessive andirrational consumption behavior that prioritizes desires rather than needs by not prioritizing benefits that tend to be wasteful, satisfaction, and self-recognition. For Islamic perspective, consumerism is forbidden because it belongs to excessive behavior, is only oriented to worldly satisfaction and arrogance. Islam teaches consumption behavior that embraces the understanding of balance in various aspects, according to needs and has a value of benefits in accordance with rationality, which means that if properly understood the concept of consumption taught by Islam then humans can limit their desires in accordance with the needs and benefits that lead to the reduced behavior wasteful, miserly, and arrogant behavior. Most of the world community has become a modern society, modernization has a positive impact in facilitating daily activities, and it is closely related to consumer behavior (consumerism) which is embraced by the society consciously or unconsciously. This research describes how Islam views the consumerism. The method that used in this research is descriptive qualitative, which describes the phenomena that exist about consumerism in Islamic perspective. The type of qualitative research that used in this study is the study of documents or texts, which are studies of written documentary material in the form of textbooks, manuscripts, articles, and its kind. Data analysis procedure before in the field is to analyze result on the preliminary observational study. The analysis during the field uses Miles and Huberman's model analysis, which suggests that the activities and analysis of qualitative data are carried out interactively and continuously until completion, thus the data is already saturated.Data analysis consist data collection, data reduction, data presentation, andanalysis/conclusion. The results shows that consumerism is excessive andirrational consumption behavior that prioritizes desires rather than needs by not prioritizing benefits that tend to be wasteful, satisfaction, and self-recognition. For Islamic perspective, consumerism is forbidden because it belongs to excessive behavior, is only oriented to worldly satisfaction and arrogance. Islam teaches consumption behavior that embraces the understanding of balance in various aspects, according to needs and has a value of benefits in accordance with rationality, which means that if properly understood the concept of consumption taught by Islam then humans can limit their desires in accordance with the needs and benefits that lead to the reduced behavior wasteful, miserly, and arrogant behavior.